2020
DOI: 10.1186/s42836-020-00035-7
|View full text |Cite
|
Sign up to set email alerts
|

Closed suction drainage offers no more clinical benefit than non-drainage after primary total knee arthroplasty with the administration of tranexamic acid in Chinese patients

Abstract: Background: If closed suction drainage (CSD) should be used after primary total knee arthroplasty (TKA), remains controversial. The current study aimed to explore whether CSD offers more clinical benefit with the administration of tranexamic acid in Chinese patients. Methods: A retrospective study was conducted on 200 patients who had received TKA. One hundred patients were placed on drainage after TKA, whereas the rest of 100 patients were not. Multiple clinical parameters were dynamically monitored and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The most important finding of the current study was that the nondrainage procedure yielded greater enhancements in pain, functioning, and proprioception compared to drainage. Our findings agree with those of previous studies [7,8,9,10,11] that have advocated for the use of the non-drainage procedure rather than drainage to provide better postoperative outcomes following TKA. Nonetheless, these previous studies mostly focused on measuring the influence of drainage on clinical outcomes such as pain level, ROM, infection rate.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most important finding of the current study was that the nondrainage procedure yielded greater enhancements in pain, functioning, and proprioception compared to drainage. Our findings agree with those of previous studies [7,8,9,10,11] that have advocated for the use of the non-drainage procedure rather than drainage to provide better postoperative outcomes following TKA. Nonetheless, these previous studies mostly focused on measuring the influence of drainage on clinical outcomes such as pain level, ROM, infection rate.…”
Section: Discussionsupporting
confidence: 92%
“…The perioperative blood loss management we used may have led to the same level of hematoma effusion, and therefore, the same level of knee swelling and ROM in both groups of the current study. Placement and removal of a drainage tube, which undoubtedly extends the duration of the inflammatory process [8,10], can be painful for patients at an early postoperative stage. More, the presence of drainage can be irritating for patients who received drainage, and therefore may excite patients' fear of drainage, and eventually exacerbate their perception of pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the incidence of DVT, Huang et al reported that in a study of 92 TKA knees with intravenous TXA, ultrasonography was performed on postoperative days 1 and 3 and at discharge, and DVT occurred in 1.1% of patients [ 31 ]. However, in reports of TKA with TXA, ultrasound was performed only when DVT was suspected [ 10 , 16 , 18 , 21 , 32 ]. Ito et al performed ultrasounds on postoperative day 7 in all patients in TKA without TXA administration and reported an overall incidence of DVT of 31.6% with a proximal incidence of 2.5% [ 33 ], similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%